Ultrahigh-Speed Swept-Source OCT Angiography in Exudative AMD - Moult, Eric; Choi, WooJhon; Waheed, Nadia K.; Adhi, Mehreen; Lee, ByungKun; Lu, Chen D.; Jayaraman, Vijaysekhar; Potsaid, Benjamin; Rosenfeld, Philip J.; Duker, Jay S.; Fujimoto, James G. (Ophthalmic surgery, lasers & imaging, 2014)
BACKGROUND AND OBJECTIVE:To investigate the potential of ultrahigh-speed swept-source optical coherence tomography angiography (OCTA) to visualize retinal and choroidal vascular changes in patients with exudative age-related macular degeneration (AMD). PATIENTS AND METHODS:Observational, prospective cross-sectional study. An ultrahigh-speed swept-source prototype was used to perform OCTA of the retinal and choriocapillaris microvasculature in 63 eyes of 32 healthy controls and 19 eyes of 15 patients with exudative AMD. Main outcome measure: qualitative comparison of the retinal and choriocapillaris microvasculature in the two groups. RESULTS:Choroidal neovascularization (CNV) was clearly visualized in 16 of the 19 eyes with exudative AMD, located above regions of severe choriocapillaris alteration. In 14 of these eyes, the CNV lesions were surrounded by regions of choriocapillaris alteration. CONCLUSION:OCTA may offer noninvasive monitoring of the retinal and choriocapillaris microvasculature in patients with CNV, which may assist in diagnosis and monitoring.[Ophthalmic Surg Lasers Imaging Retina. 2014;45:496–505.]